Chronic Critically Ill Septic Patients Exhibit Persistent Expression of Pro-Inflammatory Lipidomics. (29th May 2020) - Brown, J Christian; Kirkpatrick, Stacey; Darden, Dijoia; Loftus, Tyler; Kamel, Amir; Vanzant, Erin; Rosenthal, Martin; Falasa, Matheus; Upchurch, Gilbert
Abstract: Objectives: In order to evaluate the therapeutic potential of resolvins to reduce inflammation in CCI-PICS, we recapitulated Glue Grant leukotriene and resolvin lipidomic scores above to quantify lipidomics in severe sepsis/septic shock survivors. Methods: Ongoing University of Florida (UF) Sepsis Critical Illness Research Center (SCIRC) research studies indicate that Persistent Inflammation, Immunosuppression, and Catabolism Syndrome (PICS) occurs as a result of a self-perpetuating cycle of low-grade inflammation. However, specialized pro-resolving mediators (SPMs) – metabolically active lipid byproducts of omega-3 fatty acids – can promote inflammatory deceleration and resolution., 1 Post hoc analysis of the Glue Grant Data developed a mathematical lipidomic expression to better understand genes responsible for production and degradation of resolvins and leukotrienes., 2 Leukotriene Score = (ALOX5 * ALX5AP * LTA4H * LTB4R)/(HPGD + PTGR1 + CYP4F3) Resolvin Score = [(ALOX5 * ALOX15) * (FPR2 + GPR32 + CMKLR1)]/(HPGD + PTGR1) When the targeted genes were scored using a weighted scheme accounting for enzyme and receptor activity, patients with uncomplicated recoveries had higher resolvin scores ( P < 0.001) and lower leukotriene scores ( P < 0.001). Utilizing our PICS patient data, we recapitulated the aforementioned lipidomic scores above to quantify expression in severe sepsis/septic shock survivors. Results: Leukotriene and resolvin scores are depicted in Figure 1 at specific time points 0 (healthy controls), 3 hours, 1 and 14 days. The leukotriene score remains elevated consistent with ongoing inflammatory genotypic expression. Interestingly, the resolvin score also remains elevated in the CCI (Glue Grant complicated cohort) patient population when compared to our Rapid Recovery (RAP or uncomplicated) patients * Accompanied by two graphs depicting correlating numerical values for the aforementioned Leukotriene and Resolvin scores. Conclusions: In our patient population of sepsis survivors, the leukotriene score is similarly elevated to the complicated Glue Grant patients of polytrauma. The resolvin score, however, remains elevated in the CCI-PICS population compared to RAP; this is contrary to expected scores if resolution of inflammation is predicted. Funding Sources: University of Florida.